Anatomical Characteristics of Rhizophora’s Leaves as Mangrove Plant Adaptation at Banyuurip Mangrove Center - Yulinda Putri, Risma; Bashri, Ahmad (Jurnal Riset Biologi dan Aplikasinya, 2023)
Rhizophora is a genus of mangrove plants that dominates the Banyuurip Mangrove Center. This plant certainly has an anatomical structure as a form of adaptation to high salinity environments. The purpose of this study was to describe the anatomical characteristics of the leaves of the three Rhizophora species as an adaptation form of mangrove plants in the Banyuurip Mangrove Center and the anatomical variations of the leaves between species. This type of research was descriptive observational in the form of leaf anatomy observations using the whole mount method for longitudinal incisions and the paraffin method for transverse incisions. The results showed that there were anatomical variations among the three Rhizophora species in the Banyuurip Mangrove Center including epidermal cell size, number of epidermal cells, cork warts, number of hypodermis cell layers, hypodermis cell size, stomata size, number of stomata, stomata index, and stomata density. The anatomical characteristics of the leaves of the three Rhizophora species which act as a form of adaptation to mangrove plants are the presence of hypodermis tissue which functions to store water and salt to remove salt content in plants when they abort their leaves, low density of stomata and the presence of cuticles on the adaxial surface of leaves which play a role in reducing the rate of transpiration thus maintaining water to support plant development in saline conditions, cork warts which function as a medium for expelling salt on leaves.